Analisis Kesantunan Berbahasa dalam Video Animasi Pada Zaman Dahulu - Itsnaini Nur Khasanah; Riska Setyowati Siwi; Farida Ainur Rohmah; Rizqi Aji Wirastomo; Rizky Aprilia; Fitriani Nuraisah; Asep Purwo Yudi Utomo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines language politeness which is an important skill that needs to be instilled early on to familiarize children in communicating politely. One effective method is through children's shows that apply the principles of language politeness. In the study, the researcher used the animated video